Disaster preparedness the case of selected typhoon Sendong and Pablo victims in Barangay Hinaplanon, Iligan City, Lanao del Norte - Aberilla, Julianne Gail O.
This is a descriptive study on disaster preparedness of households living in a non-disaster prone area. It aimed to describe the disaster experience of selected households affected by Typhoon Sendong and Pablo in Barangay Hinaplanon, their disaster preparedness before the typhoons and changes in their disaster preparedness. Data was gathered through face to face interview using an interview guide with one of the household members. Eighteen households, chosen through purposive sampling, participated in the study. The study focused on seven aspects of household disaster preparedness which includes disaster program awareness, evacuation area awareness, preparation of first aid kits and emergency supplies, assignment of roles in disaster response, preparation of escape plans and drills. Data was analysed using content analysis and frequency distribution. Results show that the household respondents in Barangay Hinaplanon were all heavily affected by Typhoon Sendong while half of them did not suffer heavy losses with Typhoon Pablo. The households were mostly unprepared before Typhoon Sendong. These households had improved on their disaster preparedness with most of them showing preparedness in three to five aspects of disaster preparedness before Typhoon Pablo. Experience was found to be a major influence in household disaster preparedness. Before Typhoon Sendong, majority did not have emergency supplies, first aid kits and escape plans but their preparedness increased before Typhoon Pablo. Awareness on different disaster management programs and evacuation centers were low. A significant change was observed on the respondents? escape route planning. However, assignment of roles in the family during a disaster and emergency drills in the household did not show marked increase.